Trends in Equalized Electronegativity and its Relationship to pK and Hardness of Acids and Stability of Metal Complexes. - SEKHON, B.S. (Asian Journal of Chemistry, 2010)
Equalized electronegativity (Xeq) is an important property of a compound and tends to increase across a given period and tends to decrease down a group in case of hydrides, halides and XH4– (where X = B, Al and Ga) salts of alkali metal cations. A positive correlation (r = 0.97) exists between pK and Xeq values of binary hydrides of halogens and chalcogenides and also holds good in conjugate acid-base pairs and inorganic oxyacids. The metal complex having greater stability has greater Xeq value.